World Trade Review (Cambridge)
Includes articles written from economic, legal, political and inter-disciplinary perspectives on issues of relevance to the multilateral trading system. Priority is given to papers that, along with being academically rigorous, are also accessible to government policy officials and the wider public. The journal also includes shorter articles seeking to rebut or challenge published papers.
Keywords: Trade